Critical combinations of torsion and direct axial stress for thin-walled cylinders - Batdorf, S. B. (National Advisory Committee for Aeronautics, 1947)
A theoretical solution is presented for the determination of the combinations of direct axial stress and torsion which cause thin-walled cylinders with either simply supported or clamped edges to buckle. This theoretical solution is used in conjunction with available test data to develop empirical curves and formulas for use in design. Comparisons are made with theoretical and empirical solutions obtained in other investigations.
"Langley Memorial Aeronautical Laboratory."
Date of issue: June 1947.
Report no. NACA TN No. 1345.
Keywords: Shells (Engineering); Thin-walled structures.; Cylinders.; Strains and stresses.; Torsion.; Buckling (Mechanics); elektronické knihy; electronic books